\(\sqrt{3x^2+6x+7}+\sqrt{5x^2+10x+14}=4-2x-x^2\)
\(\Leftrightarrow\sqrt{3x^2+6x+7}+\sqrt{5x^2+10x+14}+x^2+2x-4=0\)
\(\Leftrightarrow\sqrt{3x^2+6x+7}-2+\sqrt{5x^2+10x+14}-3+x^2+2x+1=0\)
\(\Leftrightarrow\frac{3x^2+6x+7-4}{\sqrt{3x^2+6x+7}+2}+\frac{5x^2+10x+14-9}{\sqrt{5x^2+10x+14}+3}+\left(x+1\right)^2=0\)
\(\Leftrightarrow\frac{3\left(x+1\right)^2}{\sqrt{3x^2+6x+7}+2}+\frac{5\left(x+1\right)^2}{\sqrt{5x^2+10x+14}+3}+\left(x+1\right)^2=0\)
\(\Leftrightarrow\left(x+1\right)^2\left(\frac{3}{\sqrt{3x^2+6x+7}+2}+\frac{5}{\sqrt{5x^2+10x+14}+3}+1\right)=0\)
Dễ thấy: \(\frac{3}{\sqrt{3x^2+6x+7}+2}+\frac{5}{\sqrt{5x^2+10x+14}+3}+1>0\)
Nên (x+1)2=0 =>x+1=0 =>x=-1
\(\sqrt{x}\text{+}\sqrt{x\text{\text{-}}5}\text{+}\sqrt{x\text{+}7}=9\)
căn 3x bình cộng 6x cộng 7 + căn 5x bình cộng 10x cộng 14 =4 trừ 2x trừu x bình
chịu khó chút